FEATURES OF HAEMODINAMIC PARAMETRES OF PATIENTS WITH CHOLELITHYASIS BY ILLNESS AT SIMULTANEOUS OPERATIONS - Аль Ширафі Мохаммед Авад (World of Medicine and Biology, 2010)
In 42 patients cholecystectomi is executed by the opened access and in 299 – executed a laparoscopic method. Probed the indexes of hemodynamics in the day of operation, on 1 – 3 and 5 days after operative interference. It is set that laparoscopic method and traditional single-plane operations at patients from accompanied cholelithyasis illness by disorders of hemodynamics. A laparoscopic method has considerable advantages in a after operation period, namely: a pulse, systole, diastole and middle arteriotony, and also frequency of respiratory motions, during the leadthrough of laparoscopic operative interferences settled into a shape on the third days. While at traditional access to the organs of abdominal region these parameters were normalized, in swingeing majority on the fifth days of after operation period.
Keywords: simultantion of operation; cholelithyasis by illness